Seasonal changes in soccer players' body composition and dietary intake practices - Devlin, B. L.; Kingsley, M.; Leveritt, M. D.; Belski, R. (The Journal of Strength and Conditioning Research, 2017)
The aims of this study were 2-fold: to determine seasonal changes in dietary intake and body composition in elite soccer players and to evaluate the influence of self-determined individual body composition goals on dietary intake and body composition. This longitudinal, observational study assessed body composition (total mass, fat-free soft tissue mass, and fat mass) using dual-energy x-ray absorptiometry and dietary intake (energy and macronutrients) via multiple-pass 24-hour recalls, at 4 time points over a competitive season in elite soccer players from one professional club in the Australian A-League competition. Self-reported body composition goals were also recorded. Eighteen elite male soccer players took part (25 ± 5 years, 180.5 ± 7.4 cm, 75.6 ± 6.5 kg). Majority (=67%) reported the goal to maintain weight. Fat-free soft tissue mass increased from the start of preseason (55,278 ± 5,475 g) to the start of competitive season (56,784 ± 5,168 g; p < 0.001), and these gains were maintained until the end of the season. Fat mass decreased over the preseason period (10,072 ± 2,493 g to 8,712 ± 1,432 g; p < 0.001), but increased during the latter part of the competitive season. Dietary intake practices on training days were consistent over time and low compared with sport nutrition recommendations. The self-reported body composition goals did not strongly influence dietary intake practices or changes in body composition. This study has demonstrated that body composition changes over the course of a soccer season are subtle in elite soccer players despite relatively low self-reported intake of energy and carbohydrate.